Sequential fermentation with immobilized Hanseniaspora opuntiae in fungal pellets and Saccharomyces cerevisiae for reduced-ethanol wine production - Maria Trinidad Alcalá-Jimenez; Fernando Sánchez-Suárez; Sara Brunet; Raquel Muñoz-Castells; Juan Moreno; Rafael A. Peinado; Jaime Moreno-García; Teresa García-Martínez (Food Research International, 2026)

Exploring the suitability of radiative cooling: Comparing daytime cooling production with cooling demand in buildings − A European perspective - R. Vilà; A. Casasnovas; A. Castell (Energy and Buildings, 2025)

A practical guide to long-term field PAM chlorophyll fluorescence measurements: setup, installation, data processing with R package ‘LongTermPAM’ and interpretation - Chao Zhang; Erhard E. Pfündel; Jon Atherton; Juho Aalto; Jia Bai; Toivo Pohja; Paulina A. Rajewicz; Albert Porcar-Castell (Photosynthesis Research, 2025)
Pulse-amplitude modulated (PAM) chlorophyll fluorescence (ChlF) measurements provide a non-invasive method to study the regulation of the light reactions of photosynthesis in situ. PAM ChlF contributes also to the advancement of the interpretation of long-term observations of remotely sensed solar induced fluorescence by revealing the mechanistic connection between ChlF and photosynthetic function. However, long-term field PAM ChlF measurements remain uncommon due to challenges associated with the outdoor environment, instrument installation and maintenance, or data processing and interpretation. We here provide guidelines and recommendations to support long-term field installation of PAM ChlF systems, including the design of specialized field installation supports. We also introduce a dedicated R-package (LongTermPAM) to help users filter and analyse long-term data. Methods are demonstrated using two long-term datasets obtained with a MONI-PAM system (Monitoring PAM, Walz GmbH, Germany) on Scots pine and Norway spruce in a boreal forest. The LongTermPAM R-package helped filter spurious observations caused by dew, ice or snow, permitting calculation of photochemical (PQ) and non-photochemical quenching (NPQ) parameters and their associated yields. Finally, we illustrate how PQ and NPQ regulate the relationship between ChlF and photochemical yields, and discuss how variations in leaf PAR absorption, energy partitioning between photosystems II and I, and the contribution of photosystem I to the total ChlF signal can influence the interpretation of PAM ChlF, emphasizing the value of complementary measurements to capture variability in these factors. Although based on our experience with the MONI-PAM system in a boreal environment, most issues hereby addressed can be broadly applied to other long-term PAM monitoring systems and environments.

P19-34 Ontogeny of Drug-Induced Steatosis: From Key Initiating Events to Disease Phenotypes - E. López-Pascual; M. Moreno-Torres; E. Moro; P. Soluyanova; A. Rapisarda; R. Ortega-Vallbona; E. Serrano-Candelas; R. Gozalbes; R. Jover; J.V. Castell (Toxicology Letters, 2025)

P19-31 Unraveling drug-induced hepatic steatosis: clinical sub-phenotypes, prognosis prediction and identification of high-concern drugs and hazardous chemical attributes - M. Moreno-Torres; E. López-Pascual; E. Moro; A. Rapisarda; B. Lindeman; A. Verhoeven; T. Luechtefeld; E. Serrano-Candelas; H. Dirven; J.V. Castell; R. Jover (Toxicology Letters, 2025)

Differential innate immune activation by four different CpG-ODNs in porcine and murine cells: Implications for vaccine design - Giuliana Vedelago; Luz M. Palacios; Sofía D. Castell; Constanza Marin; Federico N. Ruiz Moreno; M. Esperanza Felici; Nicolás D. Dho; Daniel A. Allemandi; Santiago D. Palma; Gabriel Morón; Fernando A. Bessone; Fabrisio E. Alustiza; et al. (Research in Veterinary Science, 2025)

The acyl glucuronide of 2-(4-diethylamino-2-hydroxybenzoyl)benzoic acid: Synthesis, structural assignment, occurrence as a human phase II metabolite of Uvinul® A Plus and acute aquatic toxicity - María Payá-García; Gemma M. Rodríguez-Muñiz; Marta Moreno-Torres; Erika Moro; Lucas Santos-Juanes; Ana M. Amat; Salvador Gil; José V. Castell; Virginie Lhiaubet-Vallet; Miguel A. Miranda (Chemosphere, 2025)

Pericardium decellularization in a one-day, two-step protocol - P. López-Chicón; J. I. Rodríguez Martínez; C. Castells-Sala; L. Lopez-Puerto; L. Ruiz-Ponsell; O. Fariñas; A. Vilarrodona (Molecular and Cellular Biochemistry, 2025)

Mechanism and performance of the hydrolytic chemical recycling of polylactide catalyzed by the protic ionic liquid 2-HEAA - A. Cháfer; O. Gil-Castell; A. Björling; R. Ballesteros-Garrido; J.P. Cerisuelo-Ferriols; J.D. Badia (Resources, Conservation and Recycling, 2024)

Chemical recycling of post-consumer poly(ethylene terephthalate) (PET) driven by the protic ionic liquid 2-HEAA: Performance, kinetics and mechanism - J.D. Badia; R. Ballesteros-Garrido; A. Gamir-Cobacho; O. Gil-Castell; A. Cháfer (Journal of Environmental Chemical Engineering, 2024)

Last twenty-years activity of cardiovascular tissue banking in Barcelona - C. Castells-Sala; M. L. Pérez; E. Agustí; A. Aiti; E. Tarragona; A. Navarro; J. Tabera; O. Fariñas; J. L. Pomar; A. Vilarrodona (Cell and Tissue Banking, 2024)
The Barcelona Tissue Bank was established from the merge of two previous multi-tissue banks. Potential donors are screened by Donor Center staff and multi-tissue retrieval is performed by specialized own teams. Tissue processing and preservation is performed in clean room facilities by specialised personnel. After quality control of both donor and all tissues results, the heart valves and vascular segments are stored until medical request. The aim of this report is to present the cardiovascular tissue activity and retrospectively evaluate the outcomes of the changes performed in last 20 years. Cardiovascular tissue from 4088 donors was received, specifically 3115 hearts and 2095 vascular segments were processed and evaluated. A total of 48% of the aortic valves, 68% of the pulmonary valves and 75% of the vascular segments were suitable for transplant. The main reason for discarding tissue was macroscopic morphology followed by microbiological results, for both valves and arteries. Altogether, 4360 tissues were distributed for transplantation: 2032 (47%) vascular segments, 1545 (35%) pulmonary valves and 781 (18%) aortic valves. The most common indication for aortic valve surgery was the treatment of endocarditis, while for pulmonary valves, it was congenital malformation reconstruction. Vascular segments were mainly used for reconstruction after ischemia. During this period, a number of changes were made with the goal of enhancing tissue quality, safety and efficacy. These improvements were achieved through the use of a new antibiotic cocktail, increasing of donor age criteria and changing the microbiological control strategy.

Strategies towards thermochemical valorisation of spent coffee grounds (SCG): Kinetic analysis of the thermal and thermo-oxidative decomposition - C. Primaz; O. Gil-Castell; A. Ribes-Greus (Biomass and Bioenergy, 2023)

The photosynthetic response of spectral chlorophyll fluorescence differs across species and light environments in a boreal forest ecosystem - Paulina A. Rajewicz; Chao Zhang; Jon Atherton; Shari Van Wittenberghe; Anu Riikonen; Troy Magney; Beatriz Fernandez-Marin; Jose Ignacio Garcia Plazaola; Albert Porcar-Castell (Agricultural and Forest Meteorology, 2023)

Capture of CO2 and Water While Driving for Use in the Food and Agricultural Systems - Maria A. Barrufet; Elena M. Castell-Perez; Rosana G. Moreira (Circular Economy and Sustainability, 2022)

The in vitro assessment of the toxicity of volatile, oxidisable, redox-cycling compounds: phenols as an example - Laia Tolosa; Teresa Martínez-Sena; Johannes P. Schimming; Erika Moro; Sylvia E. Escher; Bas ter Braak; Bob van der Water; M. A. Miranda; Barbara M. A. van Vugt-Lussenburg; José V. Castell (Archives of Toxicology, 2021)
Phenols are regarded as highly toxic chemicals. Their effects are difficult to study in in vitro systems because of their ambiguous fate (degradation, auto-oxidation and volatility). In the course of in vitro studies of a series of redox-cycling phenols, we found evidences of cross-contamination in several in vitro high-throughput test systems, in particular by trimethylbenzene-1, 4-diol/trimethylhydroquinone (TMHQ) and 2,6-di-tertbutyl-4-ethylphenol (DTBEP), and investigated in detail the physicochemical basis for such phenomenon and how to prevent it. TMHQ has fast degradation kinetics followed by significant diffusion rates of the resulting quinone to adjacent wells, other degradation products being able to air-diffuse as well. DTBEP showed lower degradation kinetics, but a higher diffusion rate. In both cases the in vitro toxicity was underestimated because of a decrease in concentration, in addition to cross-contamination to neighbouring wells. We identified four degradation products for TMHQ and five for DTBEP indicating that the current effects measured on cells are not only attributable to the parent phenolic compound. To overcome these drawbacks, we investigated in detail the physicochemical changes occurring in the course of the incubation and made use of gas-permeable and non-permeable plastic seals to prevent it. Diffusion was greatly prevented by the use of both plastic seals, as revealed by GC–MS analysis. Gas non-permeable plastic seals, reduced to a minimum compounds diffusion as well oxidation and did not affect the biological performance of cultured cells. Hence, no toxicological cross-contamination was observed in neighbouring wells, thus allowing a more reliable in vitro assessment of phenol-induced toxicity.

Validation of self-reported adherence in chronic patients visiting pharmacies and factors associated with the overestimation and underestimation of good adherence - C. Valdés y Llorca; Ernesto Cortés-Castell; J. M. Ribera-Casado; P. de Lucas-Ramos; L. M. de Palacio-Guerrero; F. Mugarza-Borqué; J. L. Casteig-Ayestarán; J. Díaz-Olmo; A. Casteig-Blanco; V. F. Gil-Guillén; M. Rizo-Baeza (European Journal of Clinical Pharmacology, 2020)

Seropositivity for pathogens associated with chronic infections is a risk factor for all-cause mortality in the elderly: findings from the Memory and Morbidity in Augsburg Elderly (MEMO) Study - Marius Zeeb; Tobias Kerrinnes; Luka Cicin-Sain; Carlos A. Guzman; Wolfram Puppe; Thomas F. Schulz; Annette Peters; Klaus Berger; Stefanie Castell; André Karch (GeroScience, 2020)
Immunostimulation by chronic infection has been linked to an increased risk for different non-communicable diseases, which in turn are leading causes of death in high- and middle-income countries. Thus, we investigated if a positive serostatus for pathogens responsible for common chronic infections is individually or synergistically related to reduced overall survival in community dwelling elderly. We used data of 365 individuals from the German MEMO (Memory and Morbidity in Augsburg Elderly) cohort study with a median age of 73 years at baseline and a median follow-up of 14 years. We examined the effect of a positive serostatus at baseline for selected pathogens associated with chronic infections ( Helicobacter pylori , Borrelia burgdorferi sensu lato , Toxoplasma gondii , cytomegalovirus, Epstein-Barr virus, herpes simplex virus 1/2, and human herpesvirus 6) on all-cause mortality with multivariable parametric survival models. We found a reduced survival time in individuals with a positive serostatus for Helicobacter pylori (accelerated failure time (AFT) − 15.92, 95% CI − 29.96; − 1.88), cytomegalovirus (AFT − 22.81, 95% CI − 36.41; − 9.22) and Borrelia burgdorferi sensu lato (AFT − 25.25, 95% CI − 43.40; − 7.10), after adjusting for potential confounders. The number of infectious agents an individual was seropositive for had a linear effect on all-cause mortality (AFT per additional infection − 12.42 95% CI − 18.55; − 6.30). Our results suggest an effect of seropositivity for Helicobacter pylori , cytomegalovirus, and Borrelia burgdorferi sensu lato on all-cause mortality in older community dwelling individuals. Further research with larger cohorts and additional biomarkers is required, to assess mediators and molecular pathways of this effect.

Modeling the Transport of Human Rotavirus and Norovirus in Standardized and in Natural Soil Matrix-Water Systems - P. Gamazo; M. Victoria; J. F. Schijven; E. Alvareda; L. F. L. Tort; J. Ramos; L. A. Lizasoain; G. Sapriza; M. Castells; L. Bessone; R. Colina (Food and Environmental Virology, 2020)

Biogeochemical recuperation of lowland tropical forest during succession - Benjamin W. Sullivan; Rachel L. DuBose; Megan K. Nasto; Silvia Alvarez‐Clare; Camie M. Dencker; Fiona M. Soper; Kevin T. Shoemaker; F. Yoko Ishida; Joana Zaragoza‐Castells; Eric A. Davidson; Cory C. Cleveland (Ecology, 2019)
High rates of land conversion and land use change have vastly increased the proportion of secondary forest in the lowland tropics relative to mature forest. As secondary forests recover following abandonment, nitrogen (N) and phosphorus (P) must be present in sufficient quantities to sustain high rates of net primary production and to replenish the nutrients lost during land use prior to secondary forest establishment. Biogeochemical theory and results from individual studies suggest that N can recuperate during secondary forest recovery, especially relative to P. Here, we synthesized 23 metrics of N and P in soil and plants from 45 secondary forest chronosequences located in the wet tropics to empirically explore (1) whether there is a consistent change in nutrients and nutrient cycling processes during secondary succession in the biome; (2) which metrics of N and P in soil and plants recuperate most consistently; (3) if the recuperation of nutrients during succession approaches similar nutrient concentrations and fluxes as those in mature forest in ~100 yr following the initiation of succession; and (4) whether site characteristics, including disturbance history, climate, and soil order are significantly related to nutrient recuperation. During secondary forest succession, nine metrics of N and/or P cycling changed consistently and substantially. In most sites, N concentrations and fluxes in both plants and soil increased during secondary succession, and total P concentrations increased in surface soil. Changes in nutrient concentrations and nutrient cycling processes during secondary succession were similar whether mature forest was included or excluded from the analysis, indicating that nutrient recuperation in secondary forest leads to biogeochemical conditions that are similar to those of mature forest. Further, of the N and P metrics that recuperated, only soil total P and foliar δ 15 N were strongly influenced by site characteristics like climate, soils, or disturbance history. Predictable nutrient recuperation across a diverse and productive ecosystem may support future forest growth and could provide a means to quantify successful restoration of ecosystem function in secondary tropical forest beyond biomass or species composition.

Evaluation of Bacterial Contamination as an Indicator of Viral Contamination in a Sedimentary Aquifer in Uruguay - P. Gamazo; M. Victoria; J. F. Schijven; E. Alvareda; L. F. L. Tort; J. Ramos; L. Burutaran; M. Olivera; A. Lizasoain; G. Sapriza; M. Castells; R. Colina (Food and Environmental Virology, 2018)

A model-based assay design to reproduce in vivo patterns of acute drug-induced toxicity - Lars Kuepfer; Olivia Clayton; Christoph Thiel; Henrik Cordes; Ramona Nudischer; Lars M. Blank; Vanessa Baier; Stephane Heymans; Florian Caiment; Adrian Roth; David A. Fluri; Jens M. Kelm; et al. (Archives of Toxicology, 2018)

EACR-MRS conference on Seed and Soil: In Vivo Models of Metastasis - I. Teles Alves; N. Cohen; P. G. Ersan; R. Eyre; I. Godet; D. Holovanchuk; R. Jackstadt; L. Kyjacova; K. Mahal; A. Noguera-Castells; L. Recalde-Percaz; J. P. Sleeman (Clinical & Experimental Metastasis, 2017)

Discontinuation of pharmacological treatment of children and adolescents with attention deficit hyperactivity disorder: meta-analysis of 63 studies enrolling 11,788 patients - M. Riera; X. Castells; A. Tobias; R. Cunill; L. Blanco; D. Capellà (Psychopharmacology, 2017)

The photosynthetic cytochrome c 550 from the diatom Phaeodactylum tricornutum - Pilar Bernal-Bayard; Leonor Puerto-Galán; Inmaculada Yruela; Inés García-Rubio; Carmen Castell; José M. Ortega; Pablo J. Alonso; Mercedes Roncel; Jesús I. Martínez; Manuel Hervás; José A. Navarro (Photosynthesis Research, 2017)

MtDNA metagenomics reveals large‐scale invasion of belowground arthropod communities by introduced species - Francesco Cicconardi; Paulo A. V. Borges; Dominique Strasberg; Pedro Oromí; Heriberto López; Antonio J. Pérez‐Delgado; Juliane Casquet; Juli Caujapé‐Castells; José María Fernández‐Palacios; Christophe Thébaud; Brent C. Emerson (Molecular Ecology, 2017)
Using a series of standardized sampling plots within forest ecosystems in remote oceanic islands, we reveal fundamental differences between the structuring of aboveground and belowground arthropod biodiversity that are likely due to large‐scale species introductions by humans. Species of beetle and spider were sampled almost exclusively from single islands, while soil‐dwelling Collembola exhibited more than tenfold higher species sharing among islands. Comparison of Collembola mitochondrial metagenomic data to a database of more than 80 000 Collembola barcode sequences revealed almost 30% of sampled island species are genetically identical, or near identical, to individuals sampled from often very distant geographic regions of the world. Patterns of mt DNA relatedness among Collembola implicate human‐mediated species introductions, with minimum estimates for the proportion of introduced species on the sampled islands ranging from 45% to 88%. Our results call for more attention to soil mesofauna to understand the global extent and ecological consequences of species introductions.

The distribution of the invasive pest, rice water weevil Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae), is expanding in Europe: First record in the Balkans, confirmed by CO1 DNA barcoding - Ioannis A. Giantsis; Javier Castells Sierra; Alexandra Chaskopoulou (Phytoparasitica, 2017)

Inter-laboratory study of human in vitro toxicogenomics-based tests as alternative methods for evaluating chemical carcinogenicity: a bioinformatics perspective - R. Herwig; H. Gmuender; R. Corvi; K. M. Bloch; A. Brandenburg; J. Castell; L. Ceelen; C. Chesne; T. Y. Doktorova; D. Jennen; P. Jennings; A. Limonciel; et al. (Archives of Toxicology, 2016)

Expression of genes involved in the salicylic acid pathway in type h1 thioredoxin transiently silenced pepper plants during a begomovirus compatible interaction - Marianne S. Luna-Rivero; Cecilia Hernández-Zepeda; Hernán Villanueva-Alonzo; Yereni Minero-García; Salvador E. Castell-González; Oscar A. Moreno-Valenzuela (Molecular Genetics and Genomics, 2016)

Efficacy, safety and variability in pharmacotherapy for adults with attention deficit hyperactivity disorder: a meta-analysis and meta-regression in over 9000 patients - R. Cunill; X. Castells; A. Tobias; D. Capellà (Psychopharmacology, 2016)

Development and characterization of nuclear microsatellite markers for Parolinia ornata Webb (Brassicaceae), and cross-species amplification in all species described in the Canarian endemic genus Parolinia - M. A. González-Pérez; J. Caujapé-Castells (Conservation Genetics Resources, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

Needle terpene concentrations and emissions of two coexisting subspecies of Scots pine attacked by the pine processionary moth (Thaumetopoea pityocampa) - Ander Achotegui-Castells; Joan Llusià; José A. Hódar; Josep Peñuelas (Acta Physiologiae Plantarum, 2013)

PRI assessment of long-term changes in carotenoids/chlorophyll ratio and short-term changes in de-epoxidation state of the xanthophyll cycle - I. Filella; A. Porcar-Castell; S. Munné-Bosch; J. Bäck; M. F. Garbulsky; J. Peñuelas (International Journal of Remote Sensing, 2009)

Using temperature‐dependent changes in leaf scaling relationships to quantitatively account for thermal acclimation of respiration in a coupled global climate–vegetation model - OWEN K. ATKIN; LINDSEY J. ATKINSON; ROSIE A. FISHER; CATHERINE D. CAMPBELL; JOANA ZARAGOZA‐CASTELLS; JON W. PITCHFORD; F. IAN WOODWARD; VAUGHAN HURRY (Global Change Biology, 2008)
The response of plant respiration ( R ) to temperature is an important component of the biosphere's response to climate change. At present, most global models assume that R increases exponentially with temperature and does not thermally acclimate. Although we now know that acclimation does occur, quantitative incorporation of acclimation into models has been lacking. Using a dataset for 19 species grown at four temperatures (7, 14, 21, and 28 °C), we have assessed whether sustained differences in growth temperature systematically alter the slope and/or intercepts of the generalized log–log plots of leaf R vs. leaf mass per unit leaf area (LMA) and vs. leaf nitrogen (N) concentration. The extent to which variations in growth temperature account for the scatter observed in log–log R –LMA–N scaling relationships was also assessed. We show that thermal history accounts for up to 20% of the scatter in scaling relationships used to predict R , with the impact of thermal history on R –LMA–N generalized scaling relationships being highly predictable. This finding enabled us to quantitatively incorporate acclimation of R into a coupled global climate–vegetation model. We show that accounting for acclimation of R has negligible impact on predicted annual rates of global R , net primary productivity (NPP) or future atmospheric CO 2 concentrations. However, our analysis suggests that accounting for acclimation is important when considering carbon fluxes among thermally contrasting biomes (e.g. accounting for acclimation decreases predicted rates of R by up to 20% in high‐temperature biomes). We conclude that acclimation of R needs to be accounted for when predicting potential responses of terrestrial carbon exchange to climatic change at a regional level.

Population genetics of Matthiola bolleana (Brassicaceae) in the Canary Islands - J. L. Sánchez Doreste; J. Caujapé-Castells; J. A. Reyes-Betancort; S. Scholz (Plant Systematics and Evolution, 2006)

Geographic Variation in Alkaloid Production in Conium maculatum Populations Experiencing Differential Herbivory by Agonopterix alstroemeriana - Eva Castells; Mark A. Berhow; Steven F. Vaughn; May R. Berenbaum (Journal of Chemical Ecology, 2005)

A high blood lactate induced by heavy exercise does not affect the increase in submaximal $$\dot V{\text{O}}_2 $$ with hyperoxia - F. B. Favier; F. Prieur; O. Grataloup; T. Busso; J. Castells; C. Denis; A. Geyssant; H. Benoit (European Journal of Applied Physiology, 2005)

Molecular evidence of hybridisation between the endemic Phoenix canariensis and the widespread P. dactylifera with Random Amplified Polymorphic DNA (RAPD) markers - M. A. Gonzlez-Prez; J. Caujap-Castells; P. A. Sosa (Plant Systematics and Evolution, 2004)

A system to simulate gas exchange in humans to control quality of metabolic measurements - F. Prieur; T. Busso; J. Castells; R. Bonnefoy; H. Benoit; A. Geyssant; C. Denis (European Journal of Applied Physiology, 1998)

Responses of plasma glutamine, free tryptophan and branched-chain amino acids to prolonged exercise after a regime designed to reduce muscle glycogen - Cathy L. Zanker; Ian L. Swaine; Linda M. Castell; Eric A. Newsholme (European Journal of Applied Physiology, 1997)

Time-resolved fluoroimmunoassays with monoclonal antibodies for rapid identification of parainfluenza type 4 and mumps viruses - J. C. Hierholzer; Patricia G. Bingham; E. Castells; R. A. Coombs (Archives of Virology, 1993)